Corporate Financial Policy and the Value of Cash - FAULKENDER, Michael (Institutional Knowledge at Singapore Management University, 2006)
We examine the cross-sectional variation in the marginal value of corporate cash holdings that arises from differences in corporate financial policy. We begin by providing semi-quantitative predictions for the value of an extra dollar of cash depending upon the likely use of that dollar, and derive a set of intuitive hypotheses to test empirically. By examining the variation in excess stock returns over the fiscal year, we find that the marginal value of cash declines with larger cash holdings, higher leverage, better access to capital markets, and as firms choose greater cash distribution via dividends rather than repurchases.